Legal and Illegal Tax Evasion - Marcel Suvelea (Hyperion Economic Journal, 2013)
In the economic and social plan, tax evasion is a reality seen in various forms, such as the keeping of not realistic accounting books; willful destruction of documents that might lead to the discovery of real product deliveries, adopted prices, fees received or paid, establishing false customs declarations for the goods import or export, preparing false tax declarations, while knowingly not mentioning but a portion of the incomes. The largest tax evasion - 60% - is generated from VAT, while social contributions generate approximately 24% of the total fiscal evasion, mainly through the phenomenon of “illegal work” (employees in the underground economy). For this purpose it is necessary a deep reform of the taxes administration, mainly in the direction of increasing the degree of tax collection. The phenomenon as a whole is very difficult to control and to quantify and to this contribute also the tax laws’ peculiarities, tax policies, corruption and the standard of living